Hydropower Development, Riverine Connectivity, and Non‐sport Fish Species: criteria for Hydraulic Design of Fishways. (12th May 2016) - Laborde, A.; González, A.; Sanhueza, C.; Arriagada, P.; Wilkes, M.; Habit, E.; Link, O.
Abstract: Hydropower barriers are among the most conspicuous anthropogenic alterations to natural riverine connectivity, resulting in species‐specific effects linked to dispersal abilities, especially swimming performance. They may present a particular problem for small‐bodied 'non‐sport fish', such as those that characterize the freshwater communities of temperate regions in the Southern Hemisphere. Recent studies have suggested that nature‐like fishways could ensure passage of diverse fish assemblages through hydropower barriers. Through experiments performed in a swim tunnel, we present, for the first time, fishway design criteria for two non‐sport species endemic to Chile, a country experiencing rapid hydropower development. In`cremental velocity tests showed that Cheirodon galusdae and juveniles of Basilichthys microlepidotus were capable of very similar standardized critical swimming speeds of 69.7 and 69.6 cm s −1, respectively. When expressed in units of body lengths, C . galusdae was capable of very high critical speeds of 16.2 bl s −1, whereas for B . microlepidotus, this was 7.6 bl s −1 . However, fixed velocity tests revealed that the swimming endurance of the latter species was slightly higher. Dimensionless analysis showed a clear relationship between fatigue time and fish Froude number, similar to that already described for subcarangiforms. Based on these results, we present fishway design curves indicating a transition from sustained to prolonged swimming at a fishway length of 15 m. Our results show that the swimming capacity of these species is well‐suited to the mean flow velocity field described for nature‐like fishways. However, more work is required to understand the effects of turbulence on the passage of non‐sport species. Copyright © 2016 John Wiley & Sons, Ltd.